Multiplikasi Tanaman Murbei (Morus Sp) Dengan Pemberian BAP Pada Kultur In Vitro - Faradilla (Buletin Loupe, 2020)
Silk sarong of Samarinda is a unique sarong made from silk threat imported from China. High quality mulberry plants are needed to support silkworm cultivation (sericulture). High quality mulberry plants are produced through in vitro propagation techniques. The aim of this research was to obtain mulberry leaves (Morus Sp) which are disease-free and uniform in order to produce high quality silk thread through sericulture technique in which the feed is multiplied in vitro. This research had four stages: sterilization, production of cultivation medium of Murashige and Skoog (MS), sub-culture, observation, and data analysis. The research was designed according toCompletely Randomized Design (RAL) with one factor i.e. different concentration of BAP (control, 0.5 mg/l, 1 mg/l, and 2 mg/l) and each treatment was replicated 8 times. The findings show that 2 mg/l treatment triggered rapid sprouting, produced the highest sprout and generated the most number of leaves. The application of BAP with different concentration also increased germination rate, the height of shoot, and the number of different sprout. All treatments were unsuccessful in inducing roots.